Effect of Boron Minerals Colemanite and Ulexite on Physical, Chemical and Mechanical Properties of Cement - Ustabas, Ilker (Sustainable and Clean Buildings, 2024)
This study investigated how the boron minerals colemanite and ulexite affect the physical, chemical and mechanical properties of cement. The radioactive permeability of the mortars with added colemanite and ulexite is also studied. The initial and final setting times, volume stability, and compressive and flexural strengths are determined. Chemical and micro-structural examinations are also performed on the cements. The linear attenuation coefficients of the mortars added to colemanite and ulexite are measured. It is concluded that colemanite and ulexite can be used as an additive in the production of cement to delay initial setting time and to reduce expansion. Also, it has been determined that colemanite reduces the hydration heat of cement. The linear attenuation coefficients of the mortars added colemanite and ulexite are also increased.